Histopathological spectrum of gastrointestinal lesions - an experience in a tertiary care centre in South India - Prasaad, Priavadhana Rajan; Rao, Bheema (International Journal of Research in Medical Sciences, 2017)
Background: Gastrointestinal biopsies are the major group specimens received in the surgical pathology department. This includes endoscopic biopsies from gastric and duodenal mucosa, appendicectomies, cholecystectomies and colonoscopic biopsies. This study aims at identifying the different histopathological lesions in these specimens. Methods: The study was a retrospective study conducted in the Department of Pathology, Sree Balaji Medical College and Hospital, Chennai, Tamil Nadu, India from January 2013-January 2014. 194 gastrointestinal biopsies were included in this study. These biopsies were fixed in 10% buffered formalin and routinely processed and paraffin embedded sections were taken and stained with Hematoxylin and Eosin. The slides were interpreted and the statistical analysis of the data obtained was done. Results: The most common specimen received was appendix (39%). The next common specimen was endoscopic gastric mucosal biopsies (20%). We had 25 cholecystectomy specimens (13%) and 17 fistulous tract excisions (9%). The other specimens studied are 20 colonoscopic biopsies (10%), six esophageal mucosal biopsies (4%), four vocal cord biopsies (2%), two liver biopsies (1%), two tonsillar biopsies (1%), and one biopsy from pharynx (1%). Conclusions: Histopathological analysis of gastrointestinal lesions aids the clinicians for follow up and specific treatment. This study gives an overview of the different histopathological specimens received in the surgical pathology department and analyses the varied histomorphological diagnosis given for these specimens.